Virginitas - Murray, M. author. aut Link
VIII, 168 p. 1 illus.
Keywords: A preface is best written last, after a book is done and its author may look back to survey what he hopes he has accomplished and what he must admit he has not. In hindsight virginity by itself has seemed a very large field to till, but with that reflection also comes a sense of the awareness that a really comprehensive treatment of misgiving, that subject would somehow have to encompass an enormous ter rain, the whole length and breadth of Christianity's attitude toward sexuality from the earliest times down to the high Middle Ages. It could be argued that no small book could cover so much ground, and I would be the first to agree. As its subtitle is meant to suggest, the present work is, in at least two senses of the word, an essay: both an initial and tentative effort to get at the meaning of an extremely important but as yet unprobed medieval belief in the perfective value of the virginal life; and an interpretive study of a complex subject from a limited point of view, specifically, that in which the virgin appears in devotional literature as the bride of Christ.